ChemInform Abstract: Higher‐Order Multicomponent Reactions: Beyond Four Reactants. Issue 36 (15th August 2013) - Brauch, Sebastian; van Berkel, Sander S.; Westermann, Bernhard
Abstract Review: 55 refs.